On Systematic Design of Service-Oriented Architectures - Kanagwa, Benjamin; Mugisa, Ezra K.; van der Weide, Th.P. (My University, 2008)
We present a systematic means of designing serviceoriented systems. Because services are developed independently, with no prior knowledge about each other, there is only a limited possibility that such services use similar message templates, initiate calls to any other service, or generate messages to support desired architecture configurations. As a result, construction of service-oriented systems rely on intermediary services to preprocess, transform and route messages to appropriate locations. The paper suggests a systematic design for the intermediary services and construction of services-oriented systems using a reuse drive approach. The approach is founded on category theory- a formal foundation for capturing and preserving structures. The approach supports parallel and incremental inter-connection of services in a planned and reusable manner
Keywords: Architectures; Systematic Design